Time-averaged flow characteristics of pulsed swirling coaxial jets with annular blockage - Jufar, S.R. (Elsevier Inc., 2022)
An experimental study was conducted to investigate the mixing and time-averaged turbulence characteristics of pulsed swirling coaxial jets with annular blockage. The study was conducted using a custom-made device by pulsing the central jet using acoustic excitation. A high-speed camera was used to identify the flow structures. The mixing characteristics and the turbulence properties of the flow were studied through a hot-wire anemometer and high-speed particle image velocimetry (PIV) techniques. Flow visualization, mean velocity profiles, vorticity and Reynolds stress fields, and Lagrangian time and length scales were used to investigate the turbulence and mixing characteristics of the flow. The flow was excited under two distinct conditions. At the lower pulsation intensity, mixing was shown to improve near the exit because of the entrainment induced during the growth of the periodic vortex rings. At the higher pulsation intensity, mixing was shown to improve further downstream due to increased jet spreading caused by the breakup of the vortex rings. Investigation of the ensemble average flow field showed that the structure of the unexcited flow was altered because of the excitation. At the higher pulsation intensity, a stagnation point was formed on the centerline which was not observed in the unexcited flow and excitation at the lower pulsation intensity. Within a single period, the position of the stagnation point moved cyclically along the centerline. In comparison with the naturally evolving jets, excitation at the higher pulsation intensity has reduced the mean axial velocity allowing better mixing of the jets in the downstream area. Â© 2022 Elsevier Inc.